Exploring student profiles in statistical performance based on self‐regulation, attitudes toward statistics and computer self‐efficacy - O'Connor, Patrick A.; Graham, Agnieszka J. (Teaching statistics, 2025)
Understanding factors influencing students' success in statistics is crucial, as many psychology students struggle with the subject, affecting their academic confidence and career readiness. This study examines profiles of undergraduate psychology students learning statistics, focusing on attitudes, IT self‐efficacy, and statistical performance. A sample of 175 first‐year students completed assessments on attitudes toward statistics, academic delay of gratification, test anxiety, and computer self‐efficacy, plus an end‐of‐year exam. Latent profile analysis identified two groups: “Motivated Performers” with higher positive attitudes toward statistics, greater computer self‐efficacy, and lower statistical anxiety, and “Anxious Learners,” who scored lower in these areas. Although Motivated Performers outperformed Anxious Learners on the exam, the difference was nonsignificant. Academic delay of gratification was the only significant predictor of performance, regardless of profile membership. These findings emphasize promoting positive attitudes and I.T. confidence in statistics and highlight the importance of self‐regulatory academic behaviors in preparing students for statistics exams.